2010
DOI: 10.1159/000281833
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Prediction of Weight Loss by Leptin among Overweight Adults

Abstract: Background/Aim: Leptin plays an important role in energy metabolism. The primary objective of the study was to investigate whether baseline leptin levels predict weight loss during a dietary intervention in overweight and obese individuals. Methods: A total of 324 individuals (138 men and 186 women, aged 20–40 years, BMI 27.5–32.5) were recruited in Iceland, Ireland and Spain. The intervention lasted for 8 consecutive weeks, and subjects were instructed to follow a diet, energy restricted by 30%. Anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 121 publications
(80 reference statements)
1
12
0
Order By: Relevance
“…However, baseline triglycerides and baseline leptin were not significantly correlated. A previous study reported a positive correlation between baseline leptin and baseline triglycerides in men, but not in women, but found no significant effect of baseline triglycerides on percentage weight loss (32). Baseline leptin and changes in leptin concentrations were significant predictors, independent of weight and fat loss, of changes in several metabolic variables.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…However, baseline triglycerides and baseline leptin were not significantly correlated. A previous study reported a positive correlation between baseline leptin and baseline triglycerides in men, but not in women, but found no significant effect of baseline triglycerides on percentage weight loss (32). Baseline leptin and changes in leptin concentrations were significant predictors, independent of weight and fat loss, of changes in several metabolic variables.…”
Section: Discussionmentioning
confidence: 66%
“…Several intervention studies in adults that analyzed the effect of baseline leptin concentrations on weight loss have reported negative correlations (22,(28)(29)(30)(31)(32)(33), whereas others have found positive (33) or no (34,35) correlations. These divergent findings may be due to differences in study design (eg, intervention duration), severity of overweight, and weight loss (36), and confounders common in obese adults, such as smoking, alcohol use, medications, and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both ghrelin and leptin act on the hypothalamus, controlling energy balance by increasing and decreasing food intake, respectively [44,119]. Thus, these hormones are considered essential elements in energy metabolism, but their mechanism of action remains unclear [68,89].…”
Section: Introductionmentioning
confidence: 99%